THE EFFECT OF PROFITABILITY ON CAPITAL STRUCTURE IN PT. MAYORA INDAH TBK YEAR 2012 - 2022 - Ariska Peihan (International Journal of Integrated Science and Technology, 2023)
This study aims to assess Profit and Capital Structure at PT. Mayora Indah Tbk 2012 to 2022 through the company financial statements. The type of research used in this research is case study researchis using the SPSS software application version 23 percentage of ROE (Return On Equity) and DER (Dept to Equity Ratio), while the data analysis technique used in this research is to calculate the annualreport of PT. Mayora Indah Tbk through descriptive analysis techniques. Based on the results of calculations and data collection of the annual report of PT. Mayora Indah Tbk can be concluded that the level of target accuracy of the implementation program needs to be properly reviewed, but the profit anf capital have been running effectively by distributing annual reports from 2012 to 2022